Detection of mental disorders with the Patient Health Questionnaire in primary care settings in Nigeria - Michael O. Olatawura; Olawale Olusegun Ogunsemi; Christopher O. Alebiosu; Olufemi E. Amoran; Adekunle J. Ariba; Francis A. Oluwole; Festus Abasiubong; Adebayo R. Erinfolami (Mental Illness)
Mental disorders lead to difficulties in social, occupational and marital relations. Failure to detect mental disorder denies patients potentially effective treatment. This study aimed to assess the prevalence and nature of mental disorders at the primary care settings and the recognition of these disorders by the attending physicians. Over a period of eight weeks, consecutive and consenting patients who attended three randomly selected primary health care facilities in Sagamu Local Government Area of Ogun state were recruited and administered a questionnaire that included a socio-demographic section and Patient Health Questionnaire (PHQ). A total of 412 subjects took part in the study. Subject age ranged from 18-90 years with a mean age of 52.50±21.08 years. One hundred and seventy- six (42.7%) of the subjects were males. A total of 120 (29.1%) of the subjects had depressive disorder, 100 (24.3%) had anxiety disorder, 196 (47.6%) somatoform disorder and 104 (25.2%) met the criteria for an alcohol related problem. The PHC physicians were only able to diagnose disorders relating to mental health in 52 (12.6%) of the subjects. Health and work situations accounted for more than three-quarters of the causes of stress experienced by the subjects. We conclude that there is a high prevalence of mental disorders among patients seen in primary care settings and that a significant proportion of them are not recognized by the primary care physicians. Stress relating to health, work and financial problems is common among primary health care attendees. Physicians in primary health care should be alert to the possibility and the impact of undetected psychiatric morbidity.